The relationships between metacognitive aspects of daily activity performance and participation patterns: Older adults’ perspectives - Liron Lamash (Hong Kong Journal of Occupational Therapy)
Background Metacognitive abilities in daily functioning and their relationship to older adults’ participation have not been sufficiently explored. Prior research has mainly focused on cognitive performance without fully addressing its functional implications. Objective This descriptive quantitative study aimed to describe older adults’ self-reported everyday difficulties related to their metacognitive abilities, their participation patterns, and the correlation relationships between them. Methodology A total of 186 community-dwelling Israeli older adults (125 women; mean age 73.44yr ± 8.25) completed a demographic questionnaire, the Daily Living Questionnaire (DLQ), and the Adult Subjective Assessment of Participation (ASAP). Results Participants reported more difficulties in complex participation activities (e.g., paying bills, navigating unfamiliar environments) than in structured routine tasks. They also reported more difficulties in executive functions (EF) than in memory and executive monitoring. Cognitive difficulties were correlated with lower participation frequency ( r = −.34, p < .001), reduced activity diversity ( r = −.34, p < .001), and increased need for assistance ( r = −.41, p < .001). Conclusions Findings highlight the need to assess metacognition functionally, as cognitive challenges significantly affect participation. Integrating subjective cognitive and participation assessments may lead to better prevention and intervention strategies among the older population.